Difference between revisions of "Math 22 Derivatives of Exponential Functions"

From Math Wiki
Jump to navigation Jump to search
 
Line 40: Line 40:
 
|<math>f(x)=\frac{e^x-e^{-x}}{2}=\frac{e^x}{2}-\frac{e^{-x}}{2}=\frac{1}{2}e^x-\frac{1}{2}e^{-x}</math>
 
|<math>f(x)=\frac{e^x-e^{-x}}{2}=\frac{e^x}{2}-\frac{e^{-x}}{2}=\frac{1}{2}e^x-\frac{1}{2}e^{-x}</math>
 
|-
 
|-
|<math>f'(x)=\frac{1}{2}e^x-\frac{1}{2}(-1)e^{-x}</math>
+
|<math>f'(x)=\frac{1}{2}e^x-\frac{1}{2}(-1)e^{-x}=\frac{1}{2}e^x+\frac{1}{2}e^{-x}</math>
 
|}
 
|}
 
[[Math_22| '''Return to Topics Page''']]
 
[[Math_22| '''Return to Topics Page''']]
  
 
'''This page were made by [[Contributors|Tri Phan]]'''
 
'''This page were made by [[Contributors|Tri Phan]]'''

Latest revision as of 07:40, 11 August 2020

Derivative of the Natural Exponential Function

 Let  be a differentiable function of . Then,
 1.
 2.

Exercises Differentiate each function:

a)

Solution:  

b)

Solution:  

c)

Solution:  

d)

Solution:  

e)

Solution:  

Return to Topics Page

This page were made by Tri Phan